Optimization of mortar compressive strength prepared with waste glass aggregate and coir fiber addition using response surface methodology - Rahmawati, Cut; Handayani, Lia; Muhtadin; Faisal, Muhammad; Zardi, Muhammad; Sapuan, S.M.; Hadi, Agung Efriyo; Ahmad, Jawad; Isleem, Haytham F. (Tech Science Press, 2023)
Waste Glass (WGs) and Coir Fiber (CF) are not widely utilized, even though their silica and cellulose content can be used to create construction materials. This study aimed to optimize mortar compressive strength using Response Surface Methodology (RSM). The Central Composite Design (CCD) was applied to determine the optimization of WGs and CF addition to the mortar compressive strength. Compressive strength and microstructure testing with Scanning Electron Microscope (SEM), Fourier-transform Infrared Spectroscopy (FT-IR), and X-Ray Diffraction (XRD) were conducted to specify the mechanical ability and bonding between the matrix, CF, and WGs. The results showed that the chemical treatment of CF produced 49.15% cellulose, with an average particle size of 1521 µm. The regression of a second-order polynomial model yielded an optimum composition consisting of 12.776% WGs and 2.344% CF with a predicted compressive strength of 19.1023 MPa. C–S–H gels were identified in the mortars due to the dissolving of SiO2 in WGs and cement. The silica from WGs increased the C–S–H phase. CF plays a role in preventing, bridging, and branching micro-cracks before reaching maximum stress. WGs aggregates and chemically treated CF are suitable to be composited in mortar to increase compressive strength.